Efektivitas Model pembelajaran Search, Solve, Create and Share (SSCS) Pada Mata Pelajaran Dasar Dasar Ketenagalistrikan - Saputra, Muhammad Handika; Candra, Oriza (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This research aims to determine the improvement in student learning outcomes by using the Search, Solve, Create, and Share learning model in the Basic Electricity subject in class X TITL 2 at SMK Negeri 2 Sungai Penuh. The minimum student completion criteria (KKM) score has not been achieved due to learning factors that are still teacher-centered or conventional, thus affecting the value of student learning outcomes in the cognitive aspect. This research uses experimental research with a pre-experimental method with a one-group pretest post-test design. The object of this research is a Search, Solve, Create, and Share (SSCS) based learning model on student learning outcomes in Basic Electricity subjects. The subjects of this research were class The instrument used in this research was a student test. Based on the results obtained, the average posttest score of students has exceeded the minimum completeness requirement. Therefore, applying a Search, Solve, Create, and Share (SSCS) based learning model in the Basic Electricity subject is effective because it improves student learning outcomes with an average N-Gain Score in the high category. The percentage of classical completeness scores obtained is also high and exceeds the minimum class completeness value that has been determined. Therefore, the application of the Search, Solve, Create, and Share (SSCS) learning model is considered to be able to improve student learning outcomes.